The ultra high net worth banker's handbook - Weber, Heinrich; Meier, Stephan (Petersfield, Hampshire : Harriman House, 2009)
The Ultra High Net Worth wealth management business is complex part of modern finance. It exists within a 'client-banker-bank' triangle and is influenced by serious exogenous factors in political, economic and fiscal environments, as well as by numerous emotional, familial and personal dimensions. This book addresses these complex relationships
1. The UHNW client -- 2. UHNWI case studies -- 3. About wealthy families -- 4. Introduction to UHNW banking -- 5. The mission of the UHNW banker -- 6. Building the UHNW business -- 7. Skills -- 8. Mindset -- 9. Our personal recommendations
Includes bibliographical references (p. 253-255) and index
Keywords: Banks and banking -- Handbooks, manuals, etc; Rich people -- Finance, Personal